y - -10 = - (x - 3)
y + 10 = -x + 3
y = -x - 3
When put in point slope form, the equation is written as y minus negative 10 equals x minus 3 times -1 (y - - 10 = - (x - 3). The y minus negative 10 changes to y plus 10 (y + 10) and you distribute the right side by multiplying by negative one (-1 or simply just "-"). Then you subtract 10 from both sides, leaving us with the answer y = -x - 3.
Hope that made sense and helped.
<u>The answer is $0.20</u>
<u>When you say 3.20 ÷ 16, it gives you 0.2, but you need to add a zero at the end to make it understandable, so that is how you end up with $0.20</u>
F(x)=x^2+2x+1 & g(x)=3(x+1)^2
now, f(x)+g(x)
=x^2+2x+1+3(x+1)^2
=x^2+2x+1+3(x^2+2x+1)
=x^2+2x+1+3x^2+6x+3
=4x^2+8x+4<===answer(c)
next:
f(x)=x^2-1 & g(x)=x+3
now, f(g(x))=(x+3)^ -1
=x^2+6x+9-1
=x^2+6x+8<====answer(b)
i solve two of ur problems.
now try the 3rd one that is similar to no. 1
and try the last two urself.
11.6, if you need a decimal. it's in between 11 and 12